2015
DOI: 10.1002/bbb.1579
|View full text |Cite
|
Sign up to set email alerts
|

Simulating and evaluating best management practices for integrated landscape management scenarios in biofuel feedstock production

Abstract: Sound crop and land management strategies can maintain land productivity and improve the environmental sustainability of agricultural crop and feedstock production. This study evaluates a strategy of incorporating landscape design and management concepts into bioenergy feedstock production. It examines the effect of land conversion and agricultural best management practices (BMPs) on water quality (nutrients and suspended sediments) and hydrology. The strategy was applied to the watershed of the South Fork Iow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 38 publications
2
19
0
8
Order By: Relevance
“…According to USDA NRCS, the width of the riparian herbaceous buffer should range from about 9 to 37 m . Thirty‐meter buffers were selected because previous studies found that a 30 m buffer is more effective than a narrower one, but reduction rates remain flat when the buffer width increased beyond 30 m . The SWAT uses the vegetative filter strip (VFS) model to simulate the effect of riparian buffers on hydrology and nutrient loads .…”
Section: Methodssupporting
confidence: 68%
See 3 more Smart Citations
“…According to USDA NRCS, the width of the riparian herbaceous buffer should range from about 9 to 37 m . Thirty‐meter buffers were selected because previous studies found that a 30 m buffer is more effective than a narrower one, but reduction rates remain flat when the buffer width increased beyond 30 m . The SWAT uses the vegetative filter strip (VFS) model to simulate the effect of riparian buffers on hydrology and nutrient loads .…”
Section: Methodssupporting
confidence: 68%
“…In particular, perennial grasses, such as switchgrass, are seen as promising cellulosic biofuel feedstock . Switchgrass has also been demonstrated to be a good choice for riparian buffers because of its relatively highly effective nutrient removal …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These buffers could reduce surface runoff into streams, increase water quality, and provide corridors that allow wildlife to move between patches of forest. Ha and Wu [32] recently examined the effect of implementing riparian buffers and converting lowproductivity land to switchgrass on nutrients and suspended sediments and hydrology in the watershed of the South Fork Iowa River in Iowa by using a SWAT model. The study found that SWAT represents field buffer and riparian buffer well with its respective sub-modules.…”
Section: Future Bioenergy Landscape Challenges and Model Improvementsmentioning
confidence: 99%